British Virgin Islands-Overseas Territory of the United Kingdom : Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
The British Virgin Islands (BVI) has most of the essential elements for a suitable framework for financial supervision. There is a weakness with respect to onsite supervision of banking, insurance, and securities sectors; and there is currently no regular and comprehensive examination and compliance program in operation. Although the legal and supervisory frameworks are adequately structured, the implementation of the full range of supervisory measures has not yet been fully achieved. However, the government is implementing a comprehensive examination methodology and plan.